2011
DOI: 10.1021/bi2012977
|View full text |Cite
|
Sign up to set email alerts
|

Ribose 5-Phosphate Glycation Reduces CytochromecRespiratory Activity and Membrane Affinity

Abstract: Spontaneous glycation of bovine heart cytochrome c (cyt c) by the sugar ribose 5-phosphate (R5P) decreases the ability of the heme protein to transfer electrons in the respiratory pathway and to bind to membranes. Trypsin fragmentation studies suggest the preferential sites of glycation include Lys72 and Lys87/88 of a cationic patch involved in the association of the protein with its respiratory chain partners and with cardiolipin-containing membranes. Reaction of bovine cyt c with R5P (50 mM) for 8 h modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Both of these metabolites are closely associated with the metabolism of glycolysis [33]. As stated above, DHAP isomerizes to the glyceraldehyde 3-phosphate and participates in the glycolytic pathway [28]. Therefore, the increased level of ribose 5-phosphate and decreased level of glyceric acid and fructose in the colonic tissue of THS-induced rats suggest that the intermediates such as DHAP in glycolysis can be diverted toward the pentose phosphate pathway under the induction of THS (Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these metabolites are closely associated with the metabolism of glycolysis [33]. As stated above, DHAP isomerizes to the glyceraldehyde 3-phosphate and participates in the glycolytic pathway [28]. Therefore, the increased level of ribose 5-phosphate and decreased level of glyceric acid and fructose in the colonic tissue of THS-induced rats suggest that the intermediates such as DHAP in glycolysis can be diverted toward the pentose phosphate pathway under the induction of THS (Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that modified Cyt c exhibits peroxidase activity, but not the native protein. Similarly, ribose-5-phosphate (R5P) has also been shown to induce certain alterations in Cyt c. However, peroxidase activation required prolonged incubation period (one week or more) 23 . In addition, modification of Cyt c by homocysteine thiolactone, accumulated under hyperhomocysteinemia has also been shown to induce gross conformational alteration leading to reduction of heme moiety and peroxidase activation 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The electrostatic interaction between Cyt c and CL is believed to be responsible for anchoring the protein to IMM and optimizes ET between complex III and complex IV 31 . In fact, glycation by R5P has also been shown to weaken the ability of Cyt c to transfer electrons in respiratory pathway and to bind membranes 23 . Hence, it is possible that modifications that lead to reduction of heme in Cyt c would thereby not only disrupt normal functionality of the protein in ET process and cellular energy demands, but also help the protein shed off from IMM.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthetic origin of R5P is the pentose phosphate pathway (PPP). PPP activation is the hallmark of rapidly proliferating cells including pluripotent stem cells, cells in the blastocyst 35 and cancer cells 36 ; R5P concentration has been shown to increase 2-10 fold in some breast tumour cell lines, for instance 37 . Where there is additionally cell necrosis, as in the tumour setting, there is the possibility of even higher local R5P concentrations in the extracellular fluid.…”
mentioning
confidence: 99%